Restoring p53 function in human melanoma cells by inhibiting MDM2 and cyclin B1/CDK1-phosphorylated nuclear iASPP. - Lu, M; Breyssens, H; Salter, V; Zhong, S; Hu, Y; Baer, C; Ratnayaka, I; Sullivan, A; Brown, N; Endicott, J; Knapp, S; Kessler, B; et al. (2013)
Nearly 90% of human melanomas contain inactivated wild-type p53, the underlying mechanisms for which are not fully understood. Here, we identify that cyclin B1/CDK1-phosphorylates iASPP, which leads to the inhibition of iASPP dimerization, promotion of iASPP monomer nuclear entry, and exposure of its p53 binding sites, leading to increased p53 inhibition. Nuclear iASPP is enriched in melanoma metastasis and associates with poor patient survival. Most wild-type p53-expressing melanoma cell lines coexpress high levels of phosphorylated nuclear iASPP, MDM2, and cyclin B1. Inhibition of MDM2 and iASPP phosphorylation with small molecules induced p53-dependent apoptosis and growth suppression. Concurrent p53 reactivation and BRAFV600E inhibition achieved additive suppression in vivo, presenting an alternative for melanoma therapy.